1994
DOI: 10.1007/bf01517205
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette-Gu�rin potentiates monocyte responses to lipopolysaccharide-induced tumor necrosis factor and interleukin-1, but not interleukin-6 in bladder cancer patients

Abstract: During the past decade, particular attention has been focused on treatment of bladder cancer patients with the bacterial agent bacillus Calmette-Guérin (BCG). In these studies, bladder cancer patients were instilled with BCG (75 mg/50 ml) once per week for 6 weeks, 1-2 weeks following trans-urethral resection of the bladder. Cystoscopy was performed after 6 weeks and, unless tumor progression was present, monthly treatments were given for 1 year. Blood was drawn 2 h after the last instillation, and monocytes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…[12][13][14][15][16][69][70][71][72] Similar to other results, the production of TNF-α and IL-1β by infected macrophages increased with LPS and LPS+IFN-γ. These results also consistent with several other studies showing that BCG stimulates the production of TNF-α and IL-1β by macrophages, [73][74][75] and the stimulation is enhanced in the presence of LPS 73 and further enhanced with the presence of LPS+IFN-γ. 76,77 We also demonstrated that phagocytosis of the BCG and rBCG strains not only reduced the viability of the macrophages but also resulted in a substantial reduction in replication of the mycobacteria.…”
Section: Discussionsupporting
confidence: 93%
“…[12][13][14][15][16][69][70][71][72] Similar to other results, the production of TNF-α and IL-1β by infected macrophages increased with LPS and LPS+IFN-γ. These results also consistent with several other studies showing that BCG stimulates the production of TNF-α and IL-1β by macrophages, [73][74][75] and the stimulation is enhanced in the presence of LPS 73 and further enhanced with the presence of LPS+IFN-γ. 76,77 We also demonstrated that phagocytosis of the BCG and rBCG strains not only reduced the viability of the macrophages but also resulted in a substantial reduction in replication of the mycobacteria.…”
Section: Discussionsupporting
confidence: 93%
“…It is therefore likely that the IL-1b that induces IkBz expression in the lung epithelial cells is released only by the monocytes present in the lungs when exposed to HDM. IL-1a is also known to be released by monocytes in response to LPS (45) and has been shown to regulate allergic responses to HDM in murine lung epithelial cells (12). Similar to IL-1b, we observed IL-1a release only from HDM-treated monocytes but not from macrophages, dendritic cells, or HBECs ( Figure 5A).…”
Section: Discussionsupporting
confidence: 51%
“…After incubation with BCG, monocytes from treated patients show increased IL-1α and TNF-α production. It has been suggested that the beneficial immuno-therapeutic effects of BCG in bladder cancer patients are related to its capacity to prime macrophages to increase the release of IL-1α and TNF-α (Conti et al, 1994). uPA expression has been described as being stimulated by IL-1 (Leizer et al, 1987;Michel and Quertermous, 1989).…”
Section: Discussionmentioning
confidence: 99%